Engineering complex liver models for drug screening and infectious diseases: a biomaterials and co-culture perspective - Lin, Christine, author; Khetani, Salman R., advisor; Gustafson, Daniel, committee member; Kipper, Matthew, committee member; Pagliassotti, Michael, committee member (Colorado State University. Libraries, 2018)
In vitro liver models have many applications in disease modeling and drug screening. Micropatterned cocultures (MPCCs) of primary human hepatocytes (PHHs) and supportive stromal cells have been shown to display high hepatic functions for long-term drug and disease studies. However, MPCCs lack liver non-parenchymal cells (NPCs) and the proper microenvironmental cues that can play important roles in conditions such as drug-induced liver injury (DILI), which is the leading cause of the prelaunch attrition and post-market withdrawal of pharmaceuticals, or diseases such as viral hepatitis. Hepatitis B virus (HBV) and hepatitis C virus (HCV) infection are major health problems that affect >250 million and ~130-170 million people worldwide, respectively, and the development of therapeutics has been hindered due to the lack of models in which to study human response to virus and drugs. Thus, long-term in vitro models that can be used to study the progression of viral infection and drug pharmacodynamics are required to develop safe and efficacious therapeutics. These models must also be human-relevant due to the narrow host tropism of hepatitis B and C and differences in liver pathways across species. Thus, the goal of this dissertation is to augment the MPCC model to include the relevant substrates and cell types for the study of cell-cell interactions in diseases such as hepatitis and DILI. Biomaterials can present important microenvironmental factors that interact with cells. Chitosan and heparin polyelectrolyte multilayers (PEMs) were utilized as a substrate to present extracellular matrix (ECM) proteins and growth factors (GF) to hepatocyte cultures. Liver biomatrix (LBM) derived from human and porcine sources were also assessed as substrates since LBM contains both soluble and insoluble cues that are usually found in the liver in vivo. In addition to improving the MPCC substrate, liver NPCs, such as primary human Kupffer cells (KCs), were incorporated into the MPCC model since KCs play key roles in immune responses and inflammation. This work will be used to establish models that integrate multiple liver cell types on a physiologically-relevant substrate to study disease states such as hepatitis and DILI towards creating effective therapeutics.